Utilizing Pandan Leaves and Lime for Economical Dishwashing Soap in the Battu Winangun Area - Puspita Sari, Putri; Wulandari, Eka; Ramadhan, M. Alfarizi; Thariq, Rusyd Ath; Adrian Nova, Gitta Destalya (Jurnal Pengabdian West Science, 2026)
This community ity aims to utilize pandan leaves (Pandservice activanus amaryllifolius) and lime (Citrus aurantifolia)which are abundant in theBattu Winangun area as the main ingredients for making economical andenvironmentally friendlydishwashing soap. The method used is a participatory approach through counseling, demonstrations of manufacture, and direct training for housewives. The results show that the resulting soap has a natural fresh aroma from pandan, effective cleaning power against grease and dirt thanks to citric acid and limonene from lime, and production costs are only around 30-40% of commercial soap. The success indicator reached 85% of participants able to produce independently, with the potential for savings of up to one month's household expenses in one family. This activity has succeeded in increasing public awareness of natural products, reducing dependence on synthetic chemicals, and opening up opportunities for sustainable home businesses.
Keywords: Pandan Leaves, Lime, Dishwashing Soap, Economical, Battu Winangun